2020
DOI: 10.1021/acs.molpharmaceut.0c00743
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Impact on Interfacial Protein Aggregation and Utilization of Surface Tension to Predict Surfactant Requirements for Biological Formulations

Abstract: Biological drug products are formulated with excipients to maintain stability over the shelf life of the product. Surfactants are added to the drug product to stabilize air–water interfaces known to induce protein aggregation. Early formulation development is focused on maintaining protein conformation and colloidal stability over the course of the drug product shelf life but rarely considers stability through dose preparation and administration. Specifically, intravenous (IV) bag preparation exposes the thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…In an IV bag, protein molecules can adsorb to the air-water interface and to the inner walls of the bag 70,120 . Because there is typically an insufficient level of surfactant in IV solution to inhibit protein adsorption to interfaces 68,121 , the interfaces will be fully coated with protein films 86,122 . The mechanical shock occurring when the IV bag hits the wall in the PTS receptacle will rupture the films [77][78][79][80][81][82]84,87,108,112 .…”
Section: Potential Mechanisms For Protein Particle Formation During Pts Transportation Of IV Bagsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an IV bag, protein molecules can adsorb to the air-water interface and to the inner walls of the bag 70,120 . Because there is typically an insufficient level of surfactant in IV solution to inhibit protein adsorption to interfaces 68,121 , the interfaces will be fully coated with protein films 86,122 . The mechanical shock occurring when the IV bag hits the wall in the PTS receptacle will rupture the films [77][78][79][80][81][82]84,87,108,112 .…”
Section: Potential Mechanisms For Protein Particle Formation During Pts Transportation Of IV Bagsmentioning
confidence: 99%
“…However it is well known that mechanical shock for example, due to dropping or shipping of containers with therapeutic proteins --can cause cavitation that results in protein particle formation and aggregation, as well as oxidation [47][48][49][64][65][66] . Furthermore, dilution of protein products in IV solution typically results in concentrations of excipients (e.g., surfactants) to levels below those that are needed to stabilize proteins [67][68][69] . The diminished protein stability can result in protein aggregate formation 42,52,[67][68][69][70] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein therapeutics such as monoclonal antibodies (mAbs) have become leading candidates for the treatment of autoimmune diseases, human cancer, and infectious diseases, among other indications. , Due to mAbs’ amphiphilic nature, adsorption of proteins from aqueous bulk solution onto surfaces (air/water, solid/liquid, or oil/water) has recently gained interest in the literature. Protein molecules are exposed to several interfaces during the manufacturing of the drug substance, processing of the drug product, and transportation, storage, and clinical administration. It has been hypothesized that as proteins adsorb onto surfaces, they can denature, unfold, and aggregate at interfaces, leading to protein particulates and aggregates in the bulk solution. Aggregates, sub-visible particles, and visible particles are detrimental to a biologic drug product as they can limit product shelf-life, reduce the effective dose of the drug, and potentially implicate an immunological response. In order to enhance protein stability, protein formulations often containing excipients such as sugars, , salts, , and/or buffers ,, and surfactants are employed to minimize the undesired interaction of proteins with surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to salts, additives such as surfactants are also known to modulate the protein aggregation kinetics and the resultant aggregate morphologies. Anionic surfactants such as sodium dodecyl sulfate (SDS) have been in focus for several decades as SDS is a well-known membrane mimetic and micellar SDS is known to destabilize the protein structure, leading to the formation of aggregation-competent intermediates. It is suggested that the “hydrophobic–hydrophilic interface” on the SDS micelles facilitates the destabilization of a protein, although the extent of destabilization depends on the SDS concentration and the protein–SDS stoichiometry, which may augment or inhibit protein aggregation.…”
Section: Introductionmentioning
confidence: 99%